PERBANDINGAN KINERJA WEB SERVER PADA PENYEDIA LAYANAN CLOUD MICROSOFT AZURE DAN AMAZON WEB SERVICES - Agit Amrullah; Agung Nugroho; Zekriansyah Ramadhan (Program Studi Informatika Universitas Teknologi Sumbawa, 2023)
A web server is essential as a service so clients can access the WWW (World Wide Web) using their web browser. Apache and Nginx are the most widely used web server software in the world; apart from their easy integration into various web panels such as Cpanel, these two software have the stability that is capable of handling client requests. Microsoft Azure and Amazon Web Services, as providers of Cloud Computing Software As Service (SaaS) and Platform As Service (PaaS) services, have different performances for implementation on web servers. This study aims to analyze the performance of Apache and Nginx web servers on the Microsoft Azure and Amazon Web Services (AWS) platforms. From the analysis, the Apache web server is superior, with an average percentage margin of 7% on the Microsoft Azure platform, and Nginx is superior on the Microsoft Azure platform with a percentage margin of 8.21%.